Notes on Galápagos grenadiers (Pisces, Gadiformes, Macrouridae), with the description of a new species of Coryphaenoides - Iwamoto, Tomio (2001)
Two unusual specimens of the grenadier genus Coryphaenoides were collected by the deep-submersible vehicle Johnson Sea-Link off the Galápagos. Unlike any other member of the genus, the snout in these specimens was rounded, non-protruding, naked anteriorly and ventrally, with no tubercular scales marking the terminal and lateral angles. They are herein described as Coryphaenoides gypsochilus. Additional specimens of grenadiers were procured by the Johnson Sea- Link, including the second and third specimens of Nezumia ventralis and the first record of Caelorinchus canus from these waters. Three species and one subspecies of Galápagos grenadiers are endemic.